Chlorogenic-induced inhibition of non-small cancer cells occurs through regulation of histone deacetylase 6 - Hongtao, Liu; Xiaoqi, Guo; Junni, Liu; Feng, Xue; Guodong, Bai; Liang, Yingping (Cellular and Molecular Biology, 2018)
Chlorogenic acid (CGA), an ester with various pharmacological effects, is important in cancer therapy. However, the specific antitumor mechanism of CGA is not entirely clear, especially with respect to its suppression of non-small cell lung cancer (NSCLC). The present study was carried out to assess the effect of CGA on NSCLC, and the mechanism involved. Cell viability assay and colony formation assay revealed that CGA blocked the proliferative capacity of NSCLC cells in vitro. Results from the migration assay suggested that CGA also inhibited the migration of A549 cells. Other assays further revealed that CGA strongly and selectively inhibited histone deacetylase 6 (HDAC6) activity and suppressed the activity of matrix metalloproteinase-2 (MMP-2) through decreased expression of Ac-NF-ÎºB. Tumorigenicity assay showed that CGA also inhibited the proliferation and metabolism of NSCLC in vivo. These results indicate that CGA significantly suppresses the proliferation of NSCLC by regulating the activity of histone deacetylase 6.